Bio-petrol synthesized from rubber seed oil extracted from rubber seeds through catalytic cracking using montmorillonite - Cheow, Yin San (2010)
Currently,most of the bio-petrol is produced from the refined or edible type oils such asthe utilization of palm oil for the production of more environmental friendly bio-fuels.However,synthesizing Isooctane from rubber seed oil (RSO) extracted from rubberseeds is more favorable as RSO contains more fatty acid to be produced into bio-petrol.The rubber seeds are readily available,cheap and help to improve the socioeconomicissues.The RSO is extracted from rubber seeds using the Soxhlet Extractor with hexaneas solvent.The catalytic cracking of the mixture of 0.1L of RSO and 20g ofMontmorillonite catalyst at 980C for 2 hours is to boost up the rate of reaction ofbreaking the long chains of fatty acids.The presence of Isooctane in a sample is detectedusing Gas Chromatogram.Chromatograms for standards of different ratio mixtures ofhexane and Isooctane are to plot a calibration curve from which the Isooctane producedcan be determined.The high actual concentration of Isooctane in samples could beexplained using the cause of catalyst structure,various types of fatty acid mixturepresent in RSO and the contamination in RSO.The mass of catalyst and volume of RSOused will affect the percentage of concentration of Isooctane in samples.As aconclusion,Bio-petrol can be produced from RSO based on the presence of Isooctaneusing Montmorillonite catalyst in the catalytic cracking process. This research can befurther improved by chromatogram modification,use fresh rubber seeds for extraction,elimination of impurities and minimization of human errors.